VLSI : circuits for emerging applications - Wojcicki, Tomasz; Iniewski, Krzysztof, 1960- (Devices, circuits, and systems., 2015)
"Preface Only recently the world celebrated the 60th anniversary of the invention of the first transistor. The first integrated circuit was built a decade later, with the first microprocessor designed in the early 1970s. Today, integrated circuits are part of almost every aspect of our daily life. They help us to live longer and more comfortably, and to do more, and do it faster. And all that is possible because of the relentless search for new materials, new circuit designs, and new ideas happening on a daily basis at universities and within the industry around the globe. Proliferation of integrated circuits in our daily lives does not mean making more of the same. It is actually the opposite. It is about making more of something completely different and customized for a particular application. And today's circuit designers cannot complain about the shortage of things to work with. All leading semiconductor foundries are offering now at least six different process nodes, from 180 nm down to 16 nm, with each node having two, three, or even more flavors. There are at least three different IO voltage standards--3.3 V, 2.5 V, and 1.8 V. And apart from the mainstream CMOS process, each foundry offers more options such as GaAs, SOI, and GaN; new, even more exotic materials are not far behind. It all gives engineers an almost unlimited number of options and choices to make to achieve their objectives or their application"--